English for Young Learners: Pembelajaran Bahasa Inggris dengan “Aksi” (Aktif, Kreatif, Santai Dan Inovatif) bagi Anak-Anak Paud SS Melati Jaya di Desa Sribulan Kecamatan Buay Pemuka Bangsa Raja Kabupaten OKU Timur - Eka Agustina; Dwi Andriani; Dea Lupita Rahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2019)
This program aimed to know English learning with AKSI (Active, Creative, Relaxed and Innovative) in TK / PAUD SS Melati Jaya, BP. Raja OKU Timur. Based on the results of the teaching process in this program, it can be seen that the English learning of children with AKSI (Active, Creative, Relaxed and Innovative), through 5 method: Teaching Methods with Bilingual / bilingual concepts (English & Indonesian), 2) Student Oriented Teaching Methods, 3) Learning by Playing Teaching Methods, 4) Life Skills Teaching Methods, and 5) Fun & Easy Teaching Methods. The results of this program show that (1) The use of AKSI (Active, creative, Relaxed and Innovative) through 5 methods used in English learning can increase student motivation according to their character at an early age, (2) The application of methods found new ideas that learning that implemented with the use of learning media or teaching aids that support the achievement of learning goals and is carried out continuously and makes students not bored and very pleasant.